Investigation of wound healing activity of the flavonoid schaftoside isolated from Lychnis chalcedonica - Tatiana N. Povetyeva; Olga G. Afanasyeva; Larisa N. Zibareva; Yulia V. Nesterova; Nikolay I. Suslov; Pavel V. Kulpin; Gleb N. Zyuz`kov; Svetlana G. Krylova; Olesya V. Vsyakikh (Belgorod National Research University, 2023)
Introduction: This article studies the wound healing activity of the flavonoid schaftoside - apigenin -6-C-β-D glucopyranosyl 8-C-α-L arabinopyranoside (C26H28O14) isolated from the above-ground part of Lyсhnis chalcedonica L. Materials and Methods: The experiments were carried out on sexually mature mongrel male CD-1 mice. The wound healing effect of schaftoside was studied on a model of a plane skin wound. Schaftoside was applied externally (topically) in the form of an aqueous solution using a pipette of 100 mcl per wound at concentrations of 0.1 uG/mL, 1.5 uG/mL, 3.0 uG/mL, one time per day during the entire period of wound healing from the first day after the wound had been induced until its complete epithelialization. Aloe juice (100 mcL per wound) was used as a positive control. A solvent (water) - 100 mcL per wound - was applied to control animals. Results and Discussion: The results of our study on the model of a plane skin wound showed that the compound schaftoside isolated from Lyсhnis chalcedonica, when applied externally (topically) at concentrations of 0.1 uG/mL, 1.5 uG/mL, 3.0 uG/mL, contributes to a significant reduction in the size of plane skin wounds, comparable to the action of aloe juice (the comparison drug). The wound healing effect is more pronounced at the first, second, and third weeks of the healing process, i.e. at the stage of inflammation, proliferation, and activation of the repair process. Under the influence of schaftoside at a concentration of 3.0 uG/mL, a more complete epithelialization was recorded than in the group where the comparison drug (aloe juice) was applied. Conclusion: Our study for the first time shows a pronounced wound healing effect from aqueous solution of the flavonoid schaftoside from Lyсhnis chalcedonica on the model of a plane skin wound in mice.